Concha Bullosa Mucocele: A Case Series and Review of the Literature. Issue 4 (October 2016) - Khalife, Sarah; Marchica, Cinzia; Zawawi, Faisal; Daniel, Sam J.; Manoukian, John J.; Tewfik, Marc A.
Background: Concha bullosa mucocele is a rare diagnosis that presents as a nasal mass. It impinges on surrounding structures and can easily be mistaken for a neoplasm. Objective: The objective of this study was to shed light on this rare entity and report its diagnostic features and treatment outcomes. Methods: A case series conducted in a tertiary health care center. Demographic data, clinical presentation, imaging, cultures, and treatments were recorded. Operative video illustration and key images were obtained. A review of the literature was also performed. Results: A total of five cases were reviewed, four of which were concha bullosa mucoceles and one was a mucopyocele. Three of the patients had some form of previous nasal trauma. Headache and nasal obstruction were the most common symptoms with a nasal mass finding on physical examination. Computed tomography was used in all the patients, and magnetic resonance imaging was used in four of the five patients. Four patients had coexistent chronic rhinosinusitis, and three had positive bacterial cultures. All these patients were treated endoscopically either with middle turbinate marsupialization or subtotal resection. No recurrence has been noted thus far. Conclusion: Concha bullosa mucocele is a rare diagnosis. Imaging characteristics are helpful in considering the diagnosis, although surgical intervention is often necessary to confirm the diagnosis and treat concha bullosa mucocele.